Revitalizing the Values of Local Wisdom in the Oral Tradition of 'Nyangahatn' Dayak Kanayatn in Anthropolinguistic Perspective - Felisitas Victoria Melati; R Kunjana Rahardi (JURNAL ARBITRER, 2022)
Maintaining the value of local wisdom in a society is important to strengthen the knowledge of a community. This study aims to formulate a strategy for revitalizing the local wisdom values of the Dayak Kanayatn ‘Nyangahatn’ oral tradition. This study uses the perspective of the anthropolinguistic approach by Duranti. The type of research used is descriptive qualitative, with the Ethnographic Spradley research method which is simplified into six stages. The step taken in collecting data is to determine the informant. Data was collected by observing and interviewing informants. Next, the researcher made ethnographic notes, and again asked descriptive questions to the informants. Then, the researcher conducted a structured interview analysis, and wrote an ethnography. The research data is in the form of elaboration and description of the form of local wisdom values and the formulation of strategies for revitalizing the values of local wisdom of the Dayak Kanayatn ‘Nyangahatn’ oral tradition. The results of the study show that there are five forms of the value of local wisdom in the oral tradition of ‘Nyangahatn’; 1) The value of human relationship with God; 2) The value of human relations with others; 3) The value of human relations with ancestors/ancestors; 4) The value of a happy life for the deceased; 5) The value of human relations with the natural environment. Furthermore, the revitalization strategy can be carried out by the local community by documenting the traditions and values of local wisdom into writing in the form of books; through local arts education (studio); take action by carrying out traditional ceremonial celebrations every year; implement the values of local wisdom in life.